The effect of the economic pillars of sustainable development goals (SDGs) on millennial entrepreneurial sustainability mediated by competitiveness: Pengaruh pilar ekonomi tujuan pembangunan berkelanjutan (SDGs) terhadap keberlanjutan wirausaha milenial yang dimediasi oleh daya saing - Mustopa, Jamal; Machmud, Amir; Istikomah, Navik (Universitas Pamulang, 2024)
This research examines and analyzes the effect of the economic pillars of the sustainable development goals (SDGs) on the sustainability of millennial entrepreneurs mediated by competitiveness. The background of this research is the value of Total Early-stage Entrepreneurial Activity (TEA), which is only 8.1%, ranked 36th out of 49 countries studied. This study uses an explanatory survey method, with data collection techniques through questionnaires distributed to millennial entrepreneurs in West Java Province who take part in education and training at the Office of Cooperatives and Small Businesses, totaling 250 people. The data that has been collected is then analyzed using SEM-PLS to produce more accurate conclusions and explore the relationship between variables. The results showed that the economic pillars of sustainable development goals (SDGs) can influence the sustainability of millennial entrepreneurs mediated by competitiveness. This finding implies that it is necessary to increase competitiveness to support the economic pillars of the SDGs.